What does the UK public want farmland to look like?. (July 2021) - Rust, Niki A.; Rehackova, Lucia; Naab, Francis; Abrams, Amber; Hughes, Courtney; Merkle, Bethann Garramon; Clark, Beth; Tindale, Sophie
Abstract: As populations grow and demand for food rises, major shifts in global agri-food policy are likely to significantly impact agricultural land use. As the UK has now separated from the Common Agricultural Policy as it left the EU, Brexit offers a unique opportunity to create UK-specific agricultural policies that may dramatically shape both the countryside's appearance and the ecosystem services it provides. However, it is important to understand how the public – as taxpayers of agri-environment schemes – want the farmed countryside to look. To fill this knowledge gap, we undertook a novel mixed-methods study using a survey and collage-making workshops to understand aesthetic preferences for perceived "ideal" and "environmentally friendly" farm landscapes. Multinomial regression of data from a nationally representative survey of 2050 respondents demonstrated widespread support for agricultural landscapes containing trees and free-ranging livestock for ideal UK farm landscapes. Aesthetic preferences differed based on several socio-demographic variables, including gender, income and education. Landscapes with renewable energy technology, trees, and no livestock were perceived to be the most "environmentally friendly" farms, though wind turbines were visually unappealing. Eighty participants created collages of their ideal and environmentally friendly farming landscapes and completed a short survey to explain their choices. Qualitative thematic analysis of the collages and explanatory text found a desire for mosaic ideal farm landscapes focused either on agricultural or wild biological diversity. Results for the environmentally friendly farms reflected those in the survey. We discuss how our findings relate to implications for post-Brexit agricultural policy formation, particularly with regards to integrating public preferences around agri-food systems, to ensure tax-payers' views are considered. Highlights: We investigated what the UK public want its farmland to look like. The public liked diverse agricultural landscapes with livestock and trees. An "environmentally friendly farm" was conceptualised as having less livestock. Our findings have widespread implications for post-Brexit agricultural policy formation.